Ego at Work: The Dynamics of Defense Mechanisms within Freud’s Structural Model of the Mind — with Reference to Saadat Hasan Manto and Kartar Singh Duggal - Kaur, Khushpreet; Kumar, Sunny (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
Defense mechanisms occupy a central place in psychoanalytic theory as unconscious strategies through which the ego manages internal conflict and external stress. Rooted in Sigmund Freud’s structural model of the psyche—comprising the id, ego, and superego—these mechanisms enable the ego to negotiate instinctual drives, moral prohibitions, and the demands of reality. This article traces the development of defense mechanisms from Freud’s The Ego and the Id (1923) to Anna Freud’s The Ego and the Mechanisms of Defence (1936), examining how processes such as repression, projection, rationalization, and sublimation function as dynamic ego operations. Integrating contemporary perspectives, including George Vaillant’s hierarchical classification of defenses and insights from trauma theory and neuroscience, the paper demonstrates the continued relevance of Freud’s structural model. It further argues that literary texts—particularly the short stories of Saadat Hasan Manto and Kartar Singh Duggal—vividly dramatize ego defense processes in characters confronting trauma, moral conflict, and social disintegration. Defense mechanisms are thus best understood not in isolation but as structured ego functions reflecting the ongoing negotiation between unconscious desire, internalized morality, and external reality.